1993
DOI: 10.1007/bf00029849
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of androgenesis in white cabbage (Brassica oleracea var. capitata) anthers by low temperature and anther dissection

Abstract: Anther culture was performed on two local cultivars, Ljubljansko and Vara~dinsko, and the F lcv. Krautman (Bejo-Zaden). The effects on androgenesis of hot and cold temperature treatments and different dissections of anthers were evaluated. In contrast to cv. Krautman, cvs. Ljubljansko and Vara~dinsko produced more embryos after cold pretreatment of flower buds (4°C, 48 h) than after standard treatment (35°C, 24h). Simultaneous cutting of the anther tip and removal of the filament gave the best results in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…Cultures were carried out at a constant temperature of +27°C, and embryos emerged with an intensity dependent on the genotype. Osolnik et al (1993) put forward a view that a low-temperature shock, as well as cutting the anthers, can induce the process of androgenesis in recalcitrant genotypes of head cabbage. However, in the present experiments there was no evidence that a 'cold' thermal shock was more effective than a 'warm' shock in inducing androgenesis in anther cultures of the poorly embriogenic cultivar Maximus F 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were carried out at a constant temperature of +27°C, and embryos emerged with an intensity dependent on the genotype. Osolnik et al (1993) put forward a view that a low-temperature shock, as well as cutting the anthers, can induce the process of androgenesis in recalcitrant genotypes of head cabbage. However, in the present experiments there was no evidence that a 'cold' thermal shock was more effective than a 'warm' shock in inducing androgenesis in anther cultures of the poorly embriogenic cultivar Maximus F 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In cauliflower microspore cultures, Vyvadilova et al (1993) used a temperature of +35°C for 24 hrs, and then a temperature of +27°C until embryos had formed. Osolnik et al (1993) worked on inducing androgenesis in anther cultures of head cabbage. They found that some genotypes were recalcitrant to a high-temperature shock (+35°C); in that case, a low-temperature shock, and also cutting of anthers, induced the process of androgenesis.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…Low temperature pretreatment improves microspore embryogenesis in B. napus (Lichter 1982), B. juncea (George and Rao 1982), and B. oleracea (Osolnik et al 1993). However, low temperature treatment of the buds inhibits microspore embryogenesis in B. campestris (Keller et al 1982) and B. napus (Dunwell et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of negative effects reported, buds were put in a sealed bottle (Dunwell et al 1985) or a sealed plastic bag (Keller et al 1982) during the pretreatment. However, in the studies where promotive effects were obtained, buds were put on a piece of wet cotton (Osolnik et al 1993) or in a liquid medium (Lichter 1982) during the pretreatment. In the present study, buds were floated in a liquid medium, under the wet condition, the microspores probably remained viable for a few weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Such treatments given to donor materials (spike, inflorescence, flower bud etc.) before inoculation promote embryo induction, produce more embryos and enhance the green plant yield in anther and microspore cultures (Sato et al, 2002;Osolnik et al, 1993).…”
Section: Introductionmentioning
confidence: 99%